The notion of health in the opinion of the patients after implantation of artificial heart valves who are treated with the vitamin K antagonists (VKA) - Merklinger-Soma, Maria; Pfitzner, Roman; Dzikowska, Mirosława (Nursing Problems / Problemy Pielęgniarstwa, 2015)
Introduction. It is required for the patients who are after implantation of artificial heart valves to undertake different types of activities and their aim is to improve and maintain patients’ health. Aim. The main aim is to define the term of health in the opinion of the patients after implanting artificial heart valves who are treated with VKA. Material and methods. The data from 155 patients after implanting artificial heart valves who are treated with VKA was scrutinised. The List of Health Criteria (LKZ) written by Juczyński was used. Results. The patients highly prized the statement „it is the most important not to feel any physical ailments” and this statement referred to the criterion of health understood as the attribute. Conclusions. Ill people highly valued the criterion of health defined as the attribute which refers to the physical dimension of health and it may point out that the approach to this issue is instrumental.